2012
DOI: 10.3917/rfas.114.0114
|View full text |Cite
|
Sign up to set email alerts
|

Communes, intercommunalité et action sociale. Les contraintes d'un changement d'échelle territoriale

Abstract: Résumé Les politiques relatives à l’intercommunalité menées en France depuis une vingtaine d’années affichent explicitement le caractère solidaire de l’engagement intercommunal. Dès lors, il est possible de considérer que l’action sociale, dont l’objet consiste à réduire les inégalités et à favoriser la cohésion locale, confère à ce domaine de l’action publique une place prépondérante au sein des intercommunalités et participe à la production d’espaces solidaires que souhaite favoriser la coopération intercomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Indeed, while some analyses of specific intermunicipalities have identified the logic and strategies applied by local public actors 6 , few studies have sought to establish global statistical relationships between measurable municipalities' and intermunicipalities' characteristics and the competences transferred. Frinault and Le Saout (2011) emphasised that some rural territories -consisting of small municipalities-are, for budgetary reasons, more inclined than others to engage in policies involving the sharing or transferring of social welfare competences to the intermunicipality. Frère et al (2011) demonstrated the presence of a zoo effect of sorts within EPCIs with own fiscal powers in France.…”
Section: The Use Of Multiple Indicators and Geographical Scales In Ormentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while some analyses of specific intermunicipalities have identified the logic and strategies applied by local public actors 6 , few studies have sought to establish global statistical relationships between measurable municipalities' and intermunicipalities' characteristics and the competences transferred. Frinault and Le Saout (2011) emphasised that some rural territories -consisting of small municipalities-are, for budgetary reasons, more inclined than others to engage in policies involving the sharing or transferring of social welfare competences to the intermunicipality. Frère et al (2011) demonstrated the presence of a zoo effect of sorts within EPCIs with own fiscal powers in France.…”
Section: The Use Of Multiple Indicators and Geographical Scales In Ormentioning
confidence: 99%
“…By cooperating, municipalities transfer some of their powers to the intermunicipal level, thus 6. For example, Frinault and Le Saout (2011) argue that it is politically more costly for a mayor to transfer powers connected with citizens' associations (sport, social welfare) -which would see his or her direct interaction with the electorate reduced -than it is to transfer purely technical skills (waste management). Desage (2012) presents examples in which officially transferred skills have remained de facto the function of mayors.…”
Section: The Decentralisation Theorem Applied To Intermunicipal Coopementioning
confidence: 99%